VD_FINDINFO Jug / 2016 / 233 vom 12. Januar 2016 - VD Tribunal cantonal (2016)
CONSTATATION DES FAITS, DÉNONCIATION CALOMNIEUSE, TORT MORAL | 47 CO, 49 CO, 123 ch. 1 CP, 177 al. 2 CP, 303 ch. 1 CP, 43 CP, 48 let. c CP, 433 al. 1 CPP(CH)